2022
DOI: 10.1101/2022.03.23.22272742
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Increased Circulating miR-155 identifies a subtype of preeclamptic patients

Abstract: Preeclampsia is a heterogeneous disorder which affect maternal and fetal outcomes. The current classifications of preeclampsia such as "early- " and "late-" types, and "mild" and "severe" forms, are too imprecise to delineate the pathophysiology of preeclampsia. Here we reported that roughly one third of preeclampsia patients had high expression of maternal serum miR-155 in the case-control study and longitudinal study. The maternal serum miR-155 increased as early as 11-13+6 weeks of gestation. The patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
(43 reference statements)
0
3
0
Order By: Relevance
“…Recently, through a longitudinal study related to preeclampsia, we reported that about 30% patients who eventually developed preeclampsia show increased serum miR-155 levels as early as at 11–13 +6 gestational week and maintain high level across pregnancy, while serum miR-155 keeps low throughout normal pregnancy without significant changes as the progression of pregnancy. 22 In this study, we demonstrated that the maternal circulating miR-155 levels were elevated and highly correlated with the pl-miR-155 levels in the patients with high pl-miR-155, and miR-155 levels in serum were also significantly increased in pregnant miR-155 pl+ mice, which could be explained by the location of miR-155 overexpression on syncytiotrophoblasts of the placentas. Syncytiotrophoblasts are the largest subpopulation of placental trophoblasts and bathed in maternal blood pool 47 ; so miR-155 could be excreted into the maternal circulation continuously to activate maternal vascular endothelium to result in the manifestation of preeclampsia.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Recently, through a longitudinal study related to preeclampsia, we reported that about 30% patients who eventually developed preeclampsia show increased serum miR-155 levels as early as at 11–13 +6 gestational week and maintain high level across pregnancy, while serum miR-155 keeps low throughout normal pregnancy without significant changes as the progression of pregnancy. 22 In this study, we demonstrated that the maternal circulating miR-155 levels were elevated and highly correlated with the pl-miR-155 levels in the patients with high pl-miR-155, and miR-155 levels in serum were also significantly increased in pregnant miR-155 pl+ mice, which could be explained by the location of miR-155 overexpression on syncytiotrophoblasts of the placentas. Syncytiotrophoblasts are the largest subpopulation of placental trophoblasts and bathed in maternal blood pool 47 ; so miR-155 could be excreted into the maternal circulation continuously to activate maternal vascular endothelium to result in the manifestation of preeclampsia.…”
Section: Discussionmentioning
confidence: 57%
“…The serum collection of preeclamptic patients were collected at admission to our hospital, and the controls were collected during the routine prenatal examinations as previously described. 22…”
Section: Human Serum Sample Collectionmentioning
confidence: 99%
“…In addition, miR-155 and miR-210, which are upregulated in IH-exposed male subjects, are also increased in preeclampsia, and serve as predictive biomarkers for preeclampsia development [146,147]. miR-144, however, is downregulated in preeclamptic placentas and plays a protective role by inhibiting pro-apoptotic phosphatase and tensin homolog (PTEN) [148].…”
Section: Gestational Ih and Immune Activation During Pregnancymentioning
confidence: 99%